Medical Education in Somalia: Issues and Challenges - Dahie, Dr. Hassan (British Journal of Healthcare and Medical Research, 2022)
Abstract Background: Improving medical education has been a noble aim for the countries around the world over the past century to realize the universal health coverage. Through the continuous endeavors of the world countries and their learning institutions, tremendous advances have taken place in the field of medical education over the last five decades. However, being a low-resource and fragile country afflicted by protracted social conflicts and political fragmentation, Somalia faced difficulties in establishing its medical education institutions. Therefore, this study was intended to identify the issues and challenges of Medical education in Somalia. Methods: This cross-sectional study conducted in 2021 involved 384 teaching staff in medical and health science programs of public and private learning institutions in Somalia recruited through purposive sampling. Data were collected through participants administered questionnaire and key informant interview. The collected quantitative and qualitative data were analysed using SPSS and NVIVO software packages. Results: A sample of 384 participants (311 males and 73 females) was included in the study with mean age 33 years. Most of them had master’s degree and average teaching experience of 5 years. Majority of medicine and health sciences institutions were private-owned operating in rented campuses. The study showed that there was a significant association between campus ownership, campus adequacy, student selection policy, staff employment type, employee satisfaction with current salary and the type of institution. The major challenges faced by the medical education in Somalia include: shortage of trained competent lecturers, lack of relevant medical curricula, shortage of teaching/learning resources, lack of government oversight & licensing and lack of higher education policies. Conclusion There is a need to develop competency-based curriculum, train medical teachers on teaching approaches, avail teaching & learning resources, and invest in medical researches.